Non-fungible tokens, blockchain carbon credits, and the transition to carbon neutrality in supply chains - Luqman Hakim, Abdul Majid; Fernando, Yudi; Lim, Ming K.; Tseng, Ming-Lang (Taylor and Francis Ltd., 2025)
Achieving carbon neutrality in supply chains is a complex challenge, given the urgency of climate change mitigation. This paper explores how non-fungible tokens, carbon transparency, and blockchain carbon credits can support reaching carbon neutrality. We surveyed 140 Malaysian semiconductor firms involved in carbon-neutrality initiatives and conducted necessary condition analysis using the bottleneck technique. Our results show that non-fungible tokens enhance carbon transparency by providing traceable, verifiable carbon data. This transparency positively influences the issuance of blockchain carbon credits and carbon neutrality, though its effect is limited. Carbon transparency serves as a mediator between non-fungible tokens and carbon neutrality, underscoring its role in leveraging digital tools for effective carbon management. However, regulatory compliance and scalability challenges hinder both carbon transparency and digital transformation. This paper provides a foundation for integrating non-fungible tokens and blockchain technology into supply chains, offering policymakers pursuing transparent decarbonisation strategies valuable insights.